Goddess - Angelini, Josephine. (HarperTeen, an imprint of HarperCollinsPublishers, 2013)
"After being tricked into releasing the gods from their capitiviy on Olympus, Helen Hamilton must find a way to re-imprison them without starting a devasting war, all while fighting the ever-growing passion she feels for her forbidden love, Lucas Delos"--